2007
DOI: 10.1111/j.1600-0854.2007.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Ugo1p Is a Multipass Transmembrane Protein with a Single Carrier Domain Required for Mitochondrial Fusion

Abstract: The outer mitochondrial membrane protein Ugo1 forms a complex with the Fzo1p and Mgm1p GTPases that regulates mitochondrial fusion in yeast. Ugo1p contains two putative carrier domains (PCDs) found in mitochondrial carrier proteins (MCPs). Mitochondrial carrier proteins are multipass transmembrane proteins that actively transport molecules across the inner mitochondrial membrane. Mitochondrial carrier protein transport requires functional carrier domains with the consensus sequence PX(D/E)XX(K/R). Mutation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 68 publications
(114 reference statements)
2
50
1
Order By: Relevance
“…Metazoan mitofusins share the same topology and domain organization with yeast Fzo1, with the exception that they lack the most N-terminal coiled-coil region (24). Ugo1 is a yeast mitochondrial outer membrane protein that contains up to five transmembrane regions (20,25). Homologs of Ugo1 in higher organisms are unknown.…”
Section: Molecular Machinery Of Mitochondrial Fusionmentioning
confidence: 99%
“…Metazoan mitofusins share the same topology and domain organization with yeast Fzo1, with the exception that they lack the most N-terminal coiled-coil region (24). Ugo1 is a yeast mitochondrial outer membrane protein that contains up to five transmembrane regions (20,25). Homologs of Ugo1 in higher organisms are unknown.…”
Section: Molecular Machinery Of Mitochondrial Fusionmentioning
confidence: 99%
“…Ugo1 is a modified carrier protein in the OM that appears to operate after OM tethering (Coonrod et al, 2007;Hoppins et al, 2009). Ugo1 possesses three transmembrane domains and exposes its N-terminus to the cytosol (Coonrod et al, 2007;Hoppins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ugo1 is a modified carrier protein in the OM that appears to operate after OM tethering (Coonrod et al, 2007;Hoppins et al, 2009). Ugo1 possesses three transmembrane domains and exposes its N-terminus to the cytosol (Coonrod et al, 2007;Hoppins et al, 2009). In vitro binding assays with recombinant proteins revealed that the N-terminus of Ugo1 directly interacts with the cytosolic regions adjacent to the transmembrane domains in Fzo1 (Sesaki and Jensen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Direct interactions between Mgm1p and Fzo1p have not yet been demonstrated. In yeast, it is possible that the coordination is accomplished in part by Ugo1p which binds both Mgm1p and Fzo1p (Coonrod et al, 2007;Sesaki and Jensen, 2004). Peroxisomes participate in the metabolism of fatty acids and other metabolites.…”
Section: Non-snare-based Organelle Fusionmentioning
confidence: 99%